The Effect of Caffeine Treatment during Organogenesis Period on the Birth Weight of the Rat Fetuses (Rattus norvegicus) - Hery Wijayanto; Tri Wahyu Pangestiningsih; Erdiansyah Rahmi (Universitas Syiah Kuala, 2007)
The study was conducted to investigate the effects of caffeine treatment during organogenesis period to the fetal birth weight, using rat (Rattus norvegicus) as the animal model. Thirty-six primipararat obtained from Unit Pengembangan Hewan Percobaan, Gadjah Mada University (UPHP-GMU), 3 month old, 165-200 g body weight, were divided into 6 groups, consisted of 6 rats each. Six of the ratshave been selected based on the estrous cycles, and only rat with regular estrous were use for theexperiment. The rat then were mated, and during day 6-14 of the pregnancies were treated orally withcaffeine diluted in aquadest in dosage: placebo (1 cc aquadest) for group I (control), and 5.4, 10.8, 16.2,21.6, and 27 g/200 g body weight/day for treatment groups II-VI respectively. The pregnant rat bodyweights were determined at day 6 of pregnancies for calculating the caffeine treatment dosages. At day 20thof the pregnancies all of the pregnant rats were caesarotomized, and all of the fetuses were removed and weighed. The results showed that all of the treatment groups have significantly lower birth weightcompare to the groups control group. More over, fetal obtained from the treatment groups also showedserious subcutaneous hemorrhagic.Keywords: organogenesis, Rattus norvegicus, birth weight